2017
DOI: 10.1159/000479323
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Thoracic Spine Astrocytoma Presenting as Hydrocephalus in an Infant: A Case Report

Abstract: We present the case of an intramedullary spinal cord tumor from C7 to T4, classified as a WHO grade I pilocytic astrocytoma, manifesting solely with isolated, acute hydrocephalus and a normal neurological exam in a 5-month-old infant. We discuss the common presenting symptoms of spinal cord tumors in the pediatric population and possible anatomical explanations for this unique presentation and offer recommendations for the management of isolated hydrocephalus in an infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It is observed that there is no obvious obstructive pathology on neuroimaging in such cases of hydrocephalus and spinal tumor. 4,5,6 CSF examination of these patients showed a high concentration of proteins which can be the cause of hydrocephalus. [7][8] The presentation of hydrocephalus in these patients is usually covert.…”
Section: Introductionmentioning
confidence: 90%
“…It is observed that there is no obvious obstructive pathology on neuroimaging in such cases of hydrocephalus and spinal tumor. 4,5,6 CSF examination of these patients showed a high concentration of proteins which can be the cause of hydrocephalus. [7][8] The presentation of hydrocephalus in these patients is usually covert.…”
Section: Introductionmentioning
confidence: 90%
“…Primary spinal PA requires surgical resection similar to other intramedullary spinal tumors (7), but there is no clear evidence that adjuvant radio-and/or chemo-therapy treatments after surgery might be necessary. To date, only a few spinal cord PA, either case reports or sporadic ones, have been described in their genetic and molecular characteristic signatures (8)(9)(10)(11)(12)(13). The most recurrent genetic alterations in WHO Grade I spinal cord astrocytomas are BRAF-KIAA1549 translocation, BRAF copy number gain and the BRAFV600E single nucleotide variation.…”
mentioning
confidence: 99%